2022
DOI: 10.3390/brainsci12080995
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Myelin Oligodendrocyte Glycoprotein Immunoglobulin G and Neuronal or Glial Antibodies in the Central Nervous System: A Systematic Review

Abstract: Background: Myelin oligodendrocyte glycoprotein immunoglobulin G (MOG-IgG) has been considered a diagnostic marker for patients with demyelinating disease, termed “MOG-IgG associated disorder” (MOGAD). Recently, the coexistence of MOG-IgG and other neuronal or glial antibodies has attracted extensive attention from clinicians. In this article, we systematically review the characteristics of MOG-IgG-related antibody coexistence syndrome. Methods: Two authors independently searched PubMed for relevant studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Anti-NMDAR IgG antibodies exhibit a pathogenic nature ( 25 ). Given that patients with overlapping encephalitis frequently exhibit symptoms similar to anti-NMDAR encephalitis, including psychiatric symptoms and seizures ( 10 , 12 , 13 ), we believe that anti-NMDAR antibodies also have pathological significance in overlapping encephalitis. Furthermore, our study revealed that psychiatric symptoms and seizures were common.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Anti-NMDAR IgG antibodies exhibit a pathogenic nature ( 25 ). Given that patients with overlapping encephalitis frequently exhibit symptoms similar to anti-NMDAR encephalitis, including psychiatric symptoms and seizures ( 10 , 12 , 13 ), we believe that anti-NMDAR antibodies also have pathological significance in overlapping encephalitis. Furthermore, our study revealed that psychiatric symptoms and seizures were common.…”
Section: Discussionmentioning
confidence: 97%
“…Since Titulaer et al first reported an overlapping syndrome of anti-NMDAR and anti-MOG antibodies (8), a growing number of cases have been documented, and their clinical characteristics have become more apparent. Previous reviews have identified several features of this condition, including its higher prevalence in young men (9)(10)(11)(12)(13); symptoms similar to anti-NMDAR encephalitis, such as psychiatric symptoms and seizures (10,12,13); complex imaging findings with features of both anti-NMDAR encephalitis and MOGAD (10,12,13); and a generally favorable functional prognosis (9-13), despite the tendency for recurrence (9)(10)(11)(12). Initial treatment often involves steroids.…”
Section: Introductionmentioning
confidence: 99%